Pemberdayaan Puskesmas Sebagai Sarana Peningkatan Derajat Kesehatan Masyarakat Di Gampong Sungai Pauh Tanjung Kota Langsa - Elvina Sari; Maghrifah Jannati Ani; Inggi Puspita Sari (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Puskesmas is a health service facility that organizes public health efforts and first-level individual health efforts. Community Health Centers known as Puskesmas are First Level Health Facilities (FKTP) which are responsible for public health in their working areas in one or part of the sub-district area. In the Regulation of the Minister of Health Number 75 of 2014 concerning Community Health Centers it is stated that the Puskesmas has the function of organizing the first level of Community Health Efforts (UKM) and Individual Health Efforts (UKP). The lack of public understanding of the role of the puskesmas causes a conflict on the status of the community's health status. the inhibiting factor for community health center services is the lack of education and health information for the community on healthy lifestyles, the results of mini workshops that are not published to the surrounding community. public health. The method used is a lecture by providing counseling about the role of Puskesmas for the community to improve health status and be free from various health problems that often occur in the community. The target achieved in community service is to increase public knowledge about the function of the puskesmas which will later change people's attitudes in making changes in health status.